A thaumarchaeal provirus testifies for an ancient association of tailed viruses with archaea. (19th January 2011) - Krupovic, Mart; Spang, Anja; Gribaldo, Simonetta; Forterre, Patrick; Schleper, Christa
Abstract : Archaeal viruses, or archaeoviruses, display a wide range of virion morphotypes. Whereas the majority of those morphotypes are unique to archaeal viruses, some are more widely distributed across different cellular domains. Tailed double-stranded DNA archaeoviruses are remarkably similar to viruses of the same morphology (order Caudovirales) that infect many bacterial hosts. They have, so far, only been found in one phylum of the archaea, the Euryarchaeota, which has led to controversial hypotheses about their origin. In the present paper, we describe the identification and analysis of a putative provirus present in the genome of a mesophilic thaumarchaeon. We show that the provirus is related to tailed bacterial and euryarchaeal viruses and encodes a full complement of proteins that are required to build a tailed virion. The recently discovered wide distribution of tailed viruses in Euryarchaeota and the identification of a related provirus in Thaumarchaeota, an archaeal phylum which might have branched off before the separation of Crenarchaeota and Euryarchaeota, suggest that an association of these viruses with Archaea might be more ancient than previously anticipated.